PENGEMBANGAN GAME MONOPOLI BAHASA DADU DIGITAL BERBASIS EDUTAINMENT MATERI MENGOMENTARI PERSOALAN FAKTUAL - Al'Ilma, Verera Chintia Arifiani (Universitas Negeri Semarang, 2017)
This research is based on the lack of teacher innovation in developing media that supports learning speak Indonesian, thus causing low learning outcomes students of class V-C of Primary School Gisikdrono 02 Semarang with an average score of 61.29. The aim of this research is to develop a monopoly game of language with digital dice based edutainment material commenting factual issues in class V-C of Primary School Gisikdrono 02 Semarang. This research type is Research and Development (R&D) with waterfall model. This procedure is analysis, design, implementation, testing, and maintenance. This population is all students of grade V of Primary School Gisikdrono 02 Semarang, this sample is the students of class V-C, using random sampling technique. The result of this research is calculation of tcount which is 6,7479 bigger than ttable that is 1,68. An average increase test of 1.608695652, included in the high criterion. Student activity at meeting 1 obtained percentage score equal to 88,06%, and at meeting 2 equal to 98,22%, both included in criteria very good. The conclusion of this research is a monopoly game of language with digital dice effective use in learning speak Indonesian material commenting on factual issues and can increase student activity.